The Mental Image of Omani Identity in the English Press (1875–1950) - Kharusi, Mohammed Juma al-; Djabri, Sara (Journal of Studies in Language, Culture, and Society, 2025)
Keywords: Récits de voyage – Oman

Le sultanat d'Oman, perle de la péninsule Arabique - Cordonier, Gérald (24 heures, 2023)
Place: Genève
Keywords: Récits de voyage – Oman

Sultan in Oman - Morris, Jan (Eland, 2008)
Keywords: Récits de voyage – Oman

بدو عُمان في كتاب المستشرق ويلفرد ثيسجر: «الرّمال العربيّة» - البادي, مريم (مجلة البحث العلمي في الآداب, 2024)
تسعى هذه الدّراسة إلى رصد صورة متكاملة لبدو عُمان كما قدّمها كتاب «الرمال العربية» للمستشرق والرحّالة البريطاني ويلفريد ثيسيجر Wilfred Thesiger (1910 - 2003). وقد قضى ثيسيجر تسعَ سنوات مستكشفًا أفريقيا وبعض أقطار العالم العربيّ قبل أن يعيش مدّة خمس سنوات أُخرى (1945 – 1950) في جنوب عُمان برفقة البدو، والصّحراء.ويدين ثيسيجر لتجربته الثّريّة في اكتشاف إِحدى أقسى صحارى العَالم، والاقتراب من حياة مجتمع الهامش، إلى خصوصيّة علاقته ببدو عُمان، وعلى رأسهم «ابن كبينة» و«ابن غبيشة»، فمهّدوا له مهمّة عبور صحراء الرّبع الخالي مرّتين على نحوٍ غير مسبوق، وجسّروا المجتمعَ البدوي لمعايشة الغريب وتقبّله بينهم. كما يدين لهذه التجربة بجملتها بفضل تقريبه من أَسرار العالم الرُّوحيّ ليكشف وجهًا نقيضًا من الحياة مغايرًا للعالم المادّي المهيمن على أوروبا – كما يقول. يقدّم ثيسيجر تجربته هذه في مقالات نشرها متفرّقة قبل أن يجمعها في كتابه «الرمال العربية» (Arabian Sands). والمطّلع على هذا الكتاب يتبيّن صورةً لبدو عُمان تشفّ عن إعجاب ثيسيجر الشّديد بنبل أخلاقهم، وصبرهم وشجاعتهم وكرمهم وأمانتهم، وإيثارهم شظف العيش على رغده.لكن إلى جانب هذه الصّورة المشرقة المهيمنة على جملة تفاصيل تجربة ثيسجر بين بدو عُمان، والصّحراء، تحضر صور أُخرى تُرْسَمُ من تأفّفه من فضولِ البدو، وتنمّر بعض أطفالهم عليه لتخلّفه عن مشاركة النّاس الصّلاة، وغيرها.
Keywords: Récits de voyage – Oman

How NOT to Describe People Who Are Foreign to You: Exoticizing Omanis - Risse, Marielle (Come From Away, 2024)
I know that a travel writer, excited about a culture that is new to them, might not want to go into all these kinds of details. But when the writer was in Dhofar, they saw dozens, if not hundreds, …
Keywords: Dhofar; Récits de voyage – Oman

صورة الآخر في عادات أهل عمان وتقاليدهم في الخطاب السياحي " رحلة من الهند إلى إنجلترا لويليام هايد" أنموذجًا - الداودي, زاهر بن مرهون (مجلة أنساق في الآداب والعلوم الإنسانية, 2024)
سعت هذه الدراسة إلى دراسة صورة الآخر في عادات أهل عمان وتقاليدهم في الخطاب السياحي " رحلة مشبوهة من الهند إلى إنجلترا صورة عن الخليج في أوائل القرن التاسع عشر كيف شوه الرحالة الإنجليز تاريخ الخليج بأفكارهم المغلوطة أنموذجا"، ذلك أن دراسة الإنسان في الحقيقة هي دراسة الإنسانية جمعاء، وبما أن المكان له قيمة ثقافية تنبع من امتزاج الناس وتقاليدهم وطريقة تفكيرهم، وهو ما يعرف بحفريات المكان الذي يميز الشخصية دون غيرها، فقد هدفت الدراسة إلى إبراز صورة الآخر في عادات أهمل عمان وتقاليدهم عند هايد، وهل استطاعت هذه الصور أن تكون مصدر جذب سياحي لمنطقة الخليج العربي، لا سيما مسقط؟ وكيف استطاع هايد أن يوظف عادات الإنسان العماني وتقاليده وسلوكياته لتكون مصدر جذب سياحي للخليج العربي؟ لا سيما أن العادات والتقاليد تمثل عنصر تشويق لاكتشاف الآخر، ذلك أن الخطاب في بعض أشكاله عنصر رئيسي من عناصر الاتصال اللغوي السياحي؛ بامتلاكه استراتيجيات استطاع بها أن يحول عنصر السرد إلى أداة للتعبير عن جماليات المدينة التي زارها، معبرًا عن سلوكيات قاطنيها، ومعبرًا عن أبعادها المختلفة.وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، فتتبع الباحث التقرير ووقف عند أهم العادات والتقاليد التي ركز عليها هايد في خطابه؛ لتكون مصدرًا من مصادر جذب السياحة أو نفورها، وقد خرجت الدراسة بمجموعة من النتائج أهمها: أن هايد اعتمد في إبراز صورة الآخر على تصوير المعالم التي يشاهدها، مما أسهم في تصحيح صورة المتلقي، وتعزيز الجانب الثقافي.
Keywords: Récits de voyage – Oman

L’altérité ibadhite d’Oman selon Ibn Battuta - Merimi, Mohamed (Être étranger au Maghreb et ailleurs, 2011)
Keywords: Récits de voyage – Oman

Explorations in the North-West Indian Ocean: The Research Journeys of the Palinurus along the Omani Coast in the mid-1800s - Risse, Marielle (2022)
MARIELLE RISSE (Salalah) introduced us to Oman, a country in the Indian Ocean world that was never under foreign control. It is also the only country on the Arabic peninsula that gets monsoonal rains. Risse focused on the two expeditions of the brig Palinurus, which took place in the 1830s and 1850s and were the first explorations by English speakers to the southern coast of Oman, around Dhofar. The expeditions had the goal of investigating whether the Omani coast and hinterlands could be of use to the British government. They also wanted to buy the island Socotra from the Sultan in order to use it for steamship traffic between India and Britain. The surviving accounts of the expedition shed light on the local peoples; they spoke three different languages but left no written records. Risse was able to trace indigenous knowledge through oral history traditions, which were approximately 150 years old by the time they were written down in around 1850. These records reveal that much more water was available at the time, indicating that climate change is already significantly affecting Oman.
Keywords: Récits de voyage – Oman

من وثائق األرشيف العُماني رحلة القبطان همرتون من مسقط إلى زنجبار عام 1257ه/1841م-دراسة وتحقيق - الحاتمية, فاطمة بنت ناصر بن خلف; الطرونة, محمد سالم غثيان (مجلة أبجاث ميسان, 2022)
Keywords: Récits de voyage – Oman

سياحة إلى مسقط، عام 1325 هـ / 1907 م - انطاكي, عبد المسيح (ذاكرة عمان, 2019)
Keywords: Journalisme – Oman; Récits de voyage – Oman

Ibadism in Richard Francis Burton’s Travel Writings - Andrade Carvalho, Paula Carolina de (2023)
Keywords: Récits de voyage – Oman

عمان بعيون جزائرية 1900م- 1964 م - الجزائري, موسى بن عمر (الحياة, 2016)
Keywords: Récits de voyage – Oman

5 préjugés sur le Moyen-Orient dont je me suis débarrassée en habitant le Sultanat d'Oman - Hovington, Mylène (Huffington Post, 2016)
La destination fait peur de par sa situation géopolitique, mais si on laisse tomber quelques préjugés, il y a de vrais trésors à découvrir sous le ciel d'Arabie.
Keywords: Récits de voyage – Oman

أحداث رحلة أول حاكم عربي -عماني يزور واشنطن و دول أخرى (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان: تعتبر رحلة السلطان سعيد بن تيمور في الفترة من 9 نوفمبر 1937م إلى 13 يوليو 1938م من أهم الرحلات التاريخية على مستوى العلاقات بين حكومة مسقط وحكومات الدول التي زارها، إذ بدأ رحلته …
Keywords: Récits de voyage – Oman

الجزء الأخير من “تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا” (صحيفة أثير الإلكترونية, 2016)
– ما الأماكن التي زارها السلطان؟ وكيف كان استقبالهم له؟ – ما ” المصيبة” التي حدثت قبل سفر السلطان؟ وكم يوما أجّل سفره؟ – كيف استقبله شعبه بعد رجوع…
Keywords: Récits de voyage – Oman

الجزء التاسع من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان في فرجة سعادة السلطان على ميناء ليفربول: أرسل والي مدينة ليفربول غدوة نهار الثلاثاء يطلب إلى سعادة السلطان أن يشرف دار الولاية حتى يسير في صحبته إلى مرفأ السفن، ويفرّجه على…
Keywords: Récits de voyage – Oman

الجزء الثامن من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2016)
أثير - تاريخ عمان الجزء الثامن من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م:
Keywords: Récits de voyage – Oman

الجزء السابع من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان نواصل سرد تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م من خلال هذا الجزء السابع: في حضور سعادة السلطان مأدبة لجنة فيشمنجر: لا يخفى على من له إلمام بأحوال بلاد…
Keywords: Récits de voyage – Oman

الجزء السادس من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان:ذكرنا في ختام الجزء الخامس لرحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م تفا
Keywords: Récits de voyage – Oman

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان إعداد: نصر البوسعيدي (1) يدوّن التاريخ في صفحاته بأن العمانيين، وحكّامهم يعتبرون من أوائل العرب الذين شكلوا وفودا رسمية دبلوماسية لزيارة أوروبا، وأمريكا، تلك الدول …
Keywords: Récits de voyage – Oman

Importance scientifique, historique et culturelle des récits des voyageurs et des orientalistes occidentaux sur l’Oman - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (2016)
Keywords: Récits de voyage – Oman

L’Oman dans les récits de voyage au Moyen Âge (VIIe–XVe siècles) - Maguer-Gillon, Sterenn le (2016)
Keywords: Récits de voyage – Oman

Iqlîm 'Umân dans les sources arabes : regard de l'autre entre réalités et préjugés - Dridi, Moez (2016)
Keywords: Récits de voyage – Oman

صورة الموانئ العمانية في عيون الرحالة الأجانب - الهنائي, سالم بن حمد (2018)
Keywords: Récits de voyage – Oman

A South American view - Pacheco, Leila M. S. (2011)
Keywords: Récits de voyage – Oman

Danish and Norwegian travel accounts of Oman, 1765 -1995 - Bang, Anne K. (2011)
Keywords: Récits de voyage – Oman

The Turkish view - Gul, Zahid (2011)
Keywords: Récits de voyage – Oman

Mosaic Oman: views from India - Dietl, Gulshan (2011)
Keywords: Récits de voyage – Oman

The German view - Hoffmann-Ruf, Michaela (2011)
Keywords: Récits de voyage – Oman

The French view - Dridi, Moez (2011)
Keywords: Récits de voyage – Oman

The Dutch view - Witkam, Jan Just (2011)
Keywords: Récits de voyage – Oman

Oman: Arab historiography and Arab views - Ghazal, Amal N. (2011)
Keywords: Récits de voyage – Oman

African perspectives - Kusimba, Chapurukha M. (2011)
Keywords: Récits de voyage – Oman

Oman seen by Jewish travelers - Schreiner, Stefan (2011)
Keywords: Judaïsme – Oman; Récits de voyage – Oman

العمارة العمانية التراثية في كتب الرحالة الأجانب الذين زاروا عمان في القرنين التاسع عشر والعشرين الميالديين - الفارسي, سعيد بن عبد الله (2021)
Keywords: Récits de voyage – Oman

من رحالة شبة الجزيرة العربية الكولونيل إس. بي. مايلز ويوميات رحلة في عمان - Miles, Samuel Barrett (الدارة, 2006)
Keywords: Récits de voyage – Oman

Birkat al Mouz : l'oasis spirituelle du sultanat d'Oman - Thouroude, Guillaume (L'Harmattan, 2021)
Keywords: Récits de voyage – Oman

رحلة الكابتن فلوير 1876 عبر الساحل في نهاية عهد الحكم العماني مع ملحق الأحداث التاريخية - Floyer, Ernest Ayscoghe (الفرات للنشر والتوزيع, 2008)
Keywords: Récits de voyage – Oman

وصف الرحالة الأجانب لعمان في القرون الخمسة الأخيرة - الفلاحي, أحمد (نزوى: مجلة فصلية ثقافية, 2006)
Keywords: Récits de voyage – Oman

Islam and the particularities of the Ibadi denomination - Hoffmann, Anne; Dittrich, Priska (Universität Kassel, 2007)
A group of 29 forestry and agriculture students and faculty from the Universities of Kassel and Goettingen participated in a joint study tour to Oman from 24th of February to 10th of March 2007. The excursion´s aim was to gain first-hand impressions and knowledge on traditional and modern land- and resource use systems in Oman. Besides this thematic focus, we also tried to learn about the culture and way of living of the people in Oman. Therefore we are especially happy that we had the opportunity to exchange thoughts with Omani students from Sultan Qaboos University who joined part of our tour. This homepage is intended to present the topics that the study tour delt with as well as give some picture impressions from our two-week journey through Oman.
Keywords: Récits de voyage – Oman

British Travel Writing on Oman : Orientalism Reappraised = عمان في عيون الرحالة البريطانيين: قراءه جديدة للاستشراق - الحجري, هلال بن سعيد (النادي الثقافي, 2013)
Keywords: Récits de voyage – Oman

British travel-writing on Oman: Orientalism reappraised - Hajri, Hilal al- (Peter Lang, 2006)
Keywords: Récits de voyage – Oman

Three Views of Oman: Society and Religion, 1945–2006 - Thesiger, Wilfred; Butt, Charles; Grazda, Edward (Amp Publishing Group, 2012)
Keywords: Récits de voyage – Oman

Oman - Religion and Society through American Eyes - Grazda, Edward (Ministry of Endowments & Religious Affairs, 2009)
Keywords: Récits de voyage – Oman

Oman terre d'ibadisme - Prevost, Axel; Derriks, Axel (2012)
Keywords: Récits de voyage – Oman

الربع الخالي في الأدب الإنجليزي: نصوص شعرية - الحجري, هلال بن سعيد (دراسات في أدب عمان والخليج, 2004)
Keywords: Récits de voyage – Oman

مدخل إلى أدب الرحلات في عمان: دراسة وصفية للرحالة البريطانيين 1627-1970 - الحجري, هلال بن سعيد (دراسات في أدب عمان والخليج, 2004)
Keywords: Récits de voyage – Oman

La description du Yémen et du 'Uman dans le K. al-masalik wa-l-mamalik d'al-Bakri - Ducène, Jean-Charles (Acta Orientalia Academiae Scientiarum Hungaricae, 2004)
Keywords: Récits de voyage – Oman

Oman through British eyes : British travel writing on Oman from 1800 to 1970 - Hajri, Hilal al- (University of Warwick, 2003)
This thesis focuses on the images of Oman in British travel writing from 1800 to 1970. In texts that vary from travel accounts to sailors’ memoirs, complete travelogues, autobiographies, and letters, it looks at British representations of Oman as a place, people, and culture. It argues that these writings are heterogeneous and discontinuous throughout the periods under consideration. Offering diverse voices from British travellers, this thesis challenges Edward Said’s project in Orientalism (1978) which looks to Western discourse on the Middle East homogenisingly as Eurocentric and hostile. Chapter one explores and discusses the current Orientalist debate suggesting alternatives to the dilemma of Orientalism and providing a framework for the arguments in the ensuing chapters. Chapter two outlines the historical Omani-British relations, and examines the travel accounts and memoirs written by several British merchants and sailors who stopped in Muscat and other Omani coastal cities during their route from Britain to India and vice versa in the nineteenth century. Chapter three is concerned with the works of travellers who penetrated the Interior of Oman. James Wellsted’s Travels in Arabia (1838), Samuel Miles’ The Countries and Tribes of the Persian Gulf (1919) and other uncollected travel accounts, and Bertram Thomas’s Alarms and Excursions (1932) are investigated in this chapter. Chapter four considers the travellers who explored Dhofar in the southern Oman and the Ruba Al-Khali or the Empty Quarter. Precisely, it is devoted to Bertram Thomas’s Arabia Felix (1932) and Wilfred Thesiger’s Arabian Sands (1959). Chapter five looks at the last generation of British travellers who were in Oman from 1950 to 1970 employed either by oil companies or the Sultan Said bin Taimur. It explores Edward Henderson’s Arabian Destiny (1988), David Gwynne-James’s Letters from Oman (2001), and Ian Skeet’s Muscat and Oman (1974). This thesis concludes with final remarks on British travel writing on Oman and recommendations for future studies related to the subject. The gap of knowledge that this thesis undertakes to fill is that most of the texts under discussion have not been studied in any context.
Keywords: Récits de voyage – Oman

The way to Isfahan and Passing through Muscat - Loti, Pierre (Gerlach Press, 2021)
Keywords: Récits de voyage – Oman

Madkhal ilà Adab al-Riḥlāt fī ʿUmān. Dirāsa Waṣfiyya li’l-Raḥḥāla al-Brīṭāniyyīn, 1626-1970 - Hajri, Hilal al- (نزوى: مجلة فصلية ثقافية, 2003)
Keywords: Récits de voyage – Oman

Une nouvelle description de Ṣuḥār (ʿUmān) extraite d'un manuscrit inexploité du Kitāb Ṣuwar al-Aqālīm d'al-Iṣṭaḫrī - Ducène, Jean-Charles (Arabica, 2003)
Keywords: Récits de voyage – Oman

Nizwà fī Kitābāt al-Raḥḥālīn wa’l-Shuʿarā’ - ʿĪsā’ī, Saʿīd b. Sulaymān (Nizwà ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Nizwà, al-Fatra min 16-17 Jum. II 1422/7-8 Oct. 1998., 2001)
Keywords: Récits de voyage – Oman

Tārīkh ʿUmān fī Kitābāt baʿḍ al-Raḥḥāla al-Muslimīn - Saʿd Allāh, Abū ‘l-Qāsim (Aʿmāl al-Multaqà al-ʿIlmi al-awwal ḥawla Turāth Salṭanat ʿUmān al-Shaqīqa Qadīman wa-Ḥadīthan, 2003)
Keywords: Récits de voyage – Oman

British travellers in Oman from 1627- to 1970 - Hajri, Hilal al- (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Récits de voyage – Oman

Oman, 1965 - Wilkinson, John Craven (Al Roya Press & Publishing House, 2008)
Keywords: Récits de voyage – Oman

Oman under Arabian skies: an Arabian odyssey - Allen, Rory Patrick (Vanguard Press, 2010)
Keywords: Récits de voyage – Oman

Les tribulations du commandant Chapuy dans les principautés arabes du Golfe dans la seconde moitié du XIXe siècle: Oman – Émirats – Qatar – Bahreïn - Koweït - Béguin-Billecocq, Xavier (Relations internationales et culture, 2008)
Keywords: Récits de voyage – Oman

Others People’s Lives: Ibāḍī Communities from the Perspective of Francophone Orientalists’ Writings - Dridi, Moez (Today's perspectives on Ibadi history, 2017)
Keywords: Récits de voyage – Oman

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme – Oman; Récits de voyage – Oman

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman